2001
DOI: 10.1046/j.1523-1755.2001.00471.x
|View full text |Cite
|
Sign up to set email alerts
|

Heme protein-induced chronic renal inflammation: Suppressive effect of induced heme oxygenase-1

Abstract: We conclude that up-regulation of HO-1 occurs in the kidney in humans and rats repetitively exposed to heme proteins. Such up-regulation represents an anti-inflammatory response since the genetic deficiency of HO-1 markedly increases activation of NF-kappaB, MCP-1 expression, and tubulointerstitial cellular inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
180
0
5

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(199 citation statements)
references
References 51 publications
14
180
0
5
Order By: Relevance
“…The anti-inflammatory roles of HO-1 have been clearly demonstrated in HO-1-deficient mice, which display chronic renal inflammation (Nath et al, 2001) and enhanced secretion of pro-inflammatory cytokines from splenocytes (Kapturczak et al, 2004). We previously demonstrated that in microglia, HO-1 products (bilirubin, ferrous iron, and CO) reduce iNOS expression/NO production in response to IFN-g (Min et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The anti-inflammatory roles of HO-1 have been clearly demonstrated in HO-1-deficient mice, which display chronic renal inflammation (Nath et al, 2001) and enhanced secretion of pro-inflammatory cytokines from splenocytes (Kapturczak et al, 2004). We previously demonstrated that in microglia, HO-1 products (bilirubin, ferrous iron, and CO) reduce iNOS expression/NO production in response to IFN-g (Min et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The anti-inflammatory properties of HO-1 have been described in many disease models (6,10,123,129). HO-1 can dampen the inflammatory response indirectly (i.e., extrinsic to the MPS) by preventing tissue injury and necrotic cell death (i.e., DAMP production).…”
Section: Mp Ho-1 In Tissue Homeostasismentioning
confidence: 99%
“…Bilirubin is a powerful physiological antioxidant (3), but is neurotoxic at the high concentrations found in Criggler Najar patients and neonatal jaundice (4). CO, the second product of the reaction, is a gaseous messenger molecule that is thought to be involved in apoptosis (5), atherosclerosis (6), psoriasis (7), vascular constriction (8), cellular protection (9), and chronic renal inflammation (10). Finally, the ferrous iron released by heme oxygenase is normally recycled and serves as the major source of this metal for hemoglobin and other hemoprotein synthesis, as only 1-3% of the iron utilized daily in the synthesis of red blood cells is obtained from the diet (11).…”
mentioning
confidence: 99%